Behind a veil of obscurity - anonymity, encryption, free speech and privacy. (2017) - Bezemek, Christoph
Anonymous and encrypted communication looks back on a rich historical tradition. This paper discusses anonymity and encryption in a fundamental rights perspective, asking whether free speech and privacy entail a right to anonymous and encrypted communication while also addressing the problems posed by these modes of communication in the digital age.